2022
DOI: 10.3390/horticulturae8020134
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Antioxidant Activity and Bioactive Compounds in Eggplants Using Postharvest LEDs Irradiation

Abstract: Eggplant (Solanum melongena L.), one of the major vegetable crops, is recognized for its availability of numerous bioactive compounds and antioxidant activity. The accumulation of these compounds in plant tissues can be increased by exogenous stimuli, including light exposure. This study aimed at enhancing the antioxidant activity and bioactive compounds of eggplant using light-emitting diode (LEDs) irradiation after harvest. For this purpose, eggplant fruits were irradiated under LEDs at different wavelengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The findings were consistent with a previous study reporting that blue LED light increased the accumulation of anthocyanins and phenolic acids in Brassica juncea sprouts, and their extracts showed a higher antioxidant capacity . In addition, Jarerat et al reported that the peel of eggplant exposed to red + blue LED lights had the highest DPPH inhibition and ferric-reducing antioxidant power . As a result, for the accumulation of secondary metabolites (glucosinolates, flavonoids, and phenolic compounds) and antioxidant activity, plants exposed to a combination of red + blue LED light proved to be the most effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings were consistent with a previous study reporting that blue LED light increased the accumulation of anthocyanins and phenolic acids in Brassica juncea sprouts, and their extracts showed a higher antioxidant capacity . In addition, Jarerat et al reported that the peel of eggplant exposed to red + blue LED lights had the highest DPPH inhibition and ferric-reducing antioxidant power . As a result, for the accumulation of secondary metabolites (glucosinolates, flavonoids, and phenolic compounds) and antioxidant activity, plants exposed to a combination of red + blue LED light proved to be the most effective.…”
Section: Discussionmentioning
confidence: 99%
“… 51 In addition, Jarerat et al reported that the peel of eggplant exposed to red + blue LED lights had the highest DPPH inhibition and ferric-reducing antioxidant power. 52 As a result, for the accumulation of secondary metabolites (glucosinolates, flavonoids, and phenolic compounds) and antioxidant activity, plants exposed to a combination of red + blue LED light proved to be the most effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total phenolic and flavonoid contents were analyzed according to the method of Jarerat et al (2022) with slight modifications. One gram of lyophilized pericarp was homogenized in 80% ethanol and centrifuged at 12,000 × g for 20 min at 4°C.…”
Section: Total Phenolic Flavonoid and Anthocyanin Contents Of Litchi ...mentioning
confidence: 99%
“…The Ferric Reducing Antioxidant Power (FRAP) assay was performed according to Jarerat et al (2022) with some modifications. Briefly, a fresh working solution was prepared by mixing 25 mL of 300 mM acetate buffer (3.1 g C 2 H 3 NaO 2 •3H 2 O and 16 mL C 2 H 4 O 2 ), pH 3.6, 2.5 mL of 10 mM TPTZ (2,4,6-tripyridyl-striazine) solution, and 2.5 mL of 20 mM FeCl 3 •6H 2 O, and then warmed at 37°C.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%